Protest in the Callejón de Conchucos: An unpublished poem by Bernardino de Montoya from the early 17th century - León Gómez, Miguel Angel (1990)
The manuscript that we present and publish in part below is archived in the Manuscripts Section of the National Library of Madrid under number 3793. It has 69 useful pages and is written in verse with large, easily legible courtesan handwriting. The title is as follows; The province of Conchucos to His Excellency, Don Juan de Mendoza y Luna, Marquis of Montesclaros, Viceroy and Captain General of Peru, Tierra Firme and Chile.